2023
DOI: 10.3390/app132111669
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transition Areas on Driving Workload and Driving Behavior in Work Zones: A Naturalistic Driving Study

Sen Ma,
Jiangbi Hu,
Ronghua Wang

Abstract: Significant changes in road and traffic conditions in transition areas are key to traffic organization and guaranteeing safety in freeway work zones. Currently, most of the related studies on transition area use theoretical calculations, traffic and driving simulations, and the impact of different transition area conditions on drivers’ psychophysiological indicators and driving behavior are unclear. In this paper, the gap acceptance theory was used to establish a calculation method of the transition area lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The rst objective is to investigate the combined effect that driving mode and zone has on cognitive workload. Prior research has shown mixed ndings about the effect of level-2 automated driving on cognitive workload with studies either showing no differences between partial automation and manual driving (Lohani et (Ma et al, 2023;Shakouri et al, 2018), we expect cognitive workload to increase when transitioning from the pre-construction zone into the construction zone in both manual and level-2 mode. The second objective is to investigate the combined effect of driving mode and zone on glance allocation.…”
Section: Introductionmentioning
confidence: 59%
“…The rst objective is to investigate the combined effect that driving mode and zone has on cognitive workload. Prior research has shown mixed ndings about the effect of level-2 automated driving on cognitive workload with studies either showing no differences between partial automation and manual driving (Lohani et (Ma et al, 2023;Shakouri et al, 2018), we expect cognitive workload to increase when transitioning from the pre-construction zone into the construction zone in both manual and level-2 mode. The second objective is to investigate the combined effect of driving mode and zone on glance allocation.…”
Section: Introductionmentioning
confidence: 59%